A versatile NHC-parent silyliumylidene cation for catalytic chemo- and regioselective hydroboration - Leong, Bi-Xiang (2021)
This study describes the first use of a silicon(II) complex, NHC-parent silyliumylidene cation complex [(IMe)2SiH]I (1, IMe = :C{N(Me)C(Me)}2) as a versatile catalyst in organic synthesis. Complex 1 (loading: 10 mol %) was shown to act as an efficient catalyst (reaction time: 0.08 h, yield: 94%, TOF = 113.2 h-1; reaction time: 0.17 h, yield: 98%, TOF = 58.7 h-1) for the selective reduction of CO2 with pinacolborane (HBpin) to form the primarily reduced formoxyborane [pinBOC(═O)H]. The activity is better than the currently available base-metal catalysts used for this reaction. It also catalyzed the chemo- and regioselective hydroboration of carbonyl compounds and pyridine derivatives to form borate esters and N-boryl-1,4-dihydropyridine derivatives with quantitative conversions, respectively. Mechanistic studies show that the silicon(II) center in complex 1 activated the substrates and then mediated the catalytic hydroboration. In addition, complex 1 was slightly converted into the NHC-borylsilyliumylidene complex [(IMe)2SiBpin]I (3) in the catalysis, which was also able to mediate the catalytic hydroboration.